Differential Expression of Genes Involved in Saikosaponin Biosynthesis Between Bupleurum chinense DC. and Bupleurum scorzonerifolium Willd - Yu, Ma; Chen, Hua; Liu, Shi-Hang; Li, Yu-Chan; Sui, Chun; Hou, Da-Bin; Wei, Jian-He (Frontiers in Genetics, 2020)
Radix Bupleuri (root of Bupleurum spp.) is an important medicinal herb. Triterpenoid saponins of saikosaponins generally constitute the main class of secondary metabolites of Bupleurum genus. Its molecular regulatory mechanism of biosynthesis remains elusive. In this study, we observed significantly different saikosaponin biosynthesis between B. chinense and B. scorzonerifolium at seedling stage. The sequential and expressional characterization of 232 genes in triterpenoid saponins biosynthetic pathway including MVA pathway and MEP pathway between B. chinense and B. scorzonerifolium were also investigated. Sixty of them might involve saikosaponin biosynthesis. Manipulation of these genes might improve saikosaponin production, especially the genes of β-AS, P450, and UGT families.